The Needs and Experiences of People With Early-Stage Dementia Using an Application for Cognitive and Physical Activation in Germany: Qualitative Study - Melina Klein; Alexa von Bosse; Christophe Kunze (JMIR Aging)
Abstract BackgroundThe demand for support among people with dementia is increasing, while caregiving capacity is declining. As the trend of aging at home continues, technologies can help maintain the autonomy of people with dementia, enabling them to live independently for as long as possible. Furthermore, digital applications can have numerous positive biopsychosocial effects on the health of people with dementia, enhancing their physical, cognitive, and social functioning. ObjectiveThis study aims to investigate the needs and experiences of people with dementia regarding a prototype tablet-based application designed to promote cognitive and physical activity. MethodsWe conducted a methodical triangulation by combining semistructured interviews with people with dementia and external overt participant observation while testing a tablet-based application. A qualitative content analysis, as outlined by Kuckartz, was used to analyze the data. ResultsParticipants demonstrated varying levels of ability and prior experience with technology. While most were initially hesitant to use the tablet independently, they were more willing to try it after receiving encouragement. Some individuals required more assistance than others, indicating the need for individualized adjustments. Personal relevance to the content appeared to be crucial for cognitive tasks, as it helped to minimize overload for people with dementia. The participants appreciated social interaction with researchers and direct communication. Therefore, it is important to consider the role of personal support when developing and implementing technology. ConclusionsThe successful implementation and use of technology requires acceptance and an effective interaction between people with dementia, technology, and caregivers or caring relatives providing personal support. The acceptance of the application was found to be less influenced by the types and presentation of tasks and more by content relevance and social interaction. Ideally, one-on-one support will be provided during use, though this requires additional time and financial resources, which are often limited in caregiving settings.